Study on Awareness of Preconception Care and Reproductive Health Behaviors in Pre-honeymooners - Nam Joo Je; So Young Choi (Korean Society of Women Health Nursing, 2015)
PURPOSE: The purpose of this study was 1) to examine levels of awareness on preconception care and pregnancy, and reproductive health promoting behavior among pre-honeymooners; and 2) to explore the relationship between awareness levels of preconception care and pregnancy, and reproductive health promoting behavior. METHODS: This study was a correlation design with a total of 134 participants (67 couples of pre-honeymooners). Data were collected with questionnaire. RESULTS: Mean score of self-perception of awareness of preconception care and pregnancy was 2.82 out of 4. Content awareness level was 6.83 out of 13, and reproductive health promoting behavior score was 3.02 out of 4, indicating low to mid-level. Women reported higher scores in all variables than those in men. Self-perception awareness and content awareness of care and pregnancy had a weak positive correlation (r=.18, p=.038). Reproductive health promoting behavior was positively related to self-perception awareness of care and pregnancy (r=.33, p<.001) and content awareness of care and pregnancy (r=.23, p=.008). CONCLUSION: Based on this results, a variety of nursing intervention strategies may need to promote reproductive health behavior such as raising awareness of the preconception care and pregnancy.